Conformational Properties of Semiflexible Polymers: Numerical Simulations - Blavatska, V.; Haydukivska, K.; Holovatch, Yu. (Ukrainian Journal of Physics, 2012)
We study the conformational properties of semiflexible polymers within the lattice model of self-avoiding random walks (SAW) with bending energy ε that depends on the orientation between directions of two consecutive steps. We apply the pruned-enriched Rosenbluth method (PERM). Both the cases of bending preference (ε < 0) and unfavorableness (ε > 0) are analyzed, and details of the "coil-to-rod" transition, as well as properties of the "superflexible" state, are discussed.